The Fictional Rabbi's Spouse - Zucker, David J. (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2024)
This article focuses primarily on 21st-century novels and short stories situated in America, although it also occasionally refers to life in Great Britain. It first explores male rabbis' spouses in fiction, examining how these characters navigate undefined roles and experience isolation within their communities. The literature suggests that male rabbis’ spouses face three options: to be highly involved in their husband’s congregation, to be the “Rebbetzin,” whether that term is used or not; to be minimally involved, to be simply the rabbi’s wife; or to find a middle path. The analysis then turns to the spouses of women rabbis in fiction, investigating whether they face similar challenges or encounter different expectations. Finally, the article compares these two experiences, revealing significant gender disparities in the expectations placed upon rabbinic spouses and the ways they negotiate their positions within religious communities.